Energy storage system planning and software GUI development - Quay, Sean Tzhi Wen (Nanyang Technological University, 2023)
The growing usage of renewable energy led to an increased demand for Energy Storage Systems (ESS). ESS are deployed in power distribution systems to reduce the effects of the intermittent nature of certain renewable energy sources. In this paper, a model is created for optimal ESS planning in a system, while factoring in real-world parameters and constraints of PV and ESS distribution. The model will be implemented into the form of an algorithm and simulated to showcase its effectiveness. The output data will be displayed on a developed Graphical User Interface (GUI) for a comparison between the graphical data. The resultant data will prove that the proposed model is an effective approach for the reduction of investment costs while maximising operational output.